Preliminary study in discovering 2-geranylphenol from Lansium domesticum leaves as oxidation and tyrosinase inhibitor for anti-aging and skin whitening agents: experimental and theoretical study - Abdul Razak, Nur Diana; Abdullah, Erna Normaya; Mat Piah, Mohd Bijarimi; Yunus, Kamaruzzaman; Ahmad, Mohammad Norazmi (Universiti Kuala Lumpur Branch Campus Malaysian Institute of Chemical and Bioengineering Technology, 2019)
Antioxidant and tyrosinase inhibitor have been recognized as one of the most important ingredients used in cosmetic industries. These ingredients are commonly utilized to counter skin concern faced by middleaged woman regarding aging and hyperpigmentation problems. Phenolic compounds were identified to be one of the effective compound that can exert both antioxidant and anti-tyrosinase activities. Therefore, this research sought to identify a novel phenolic compound from Lansium domestium (L. domesticum) leaves as a new potential antioxidant and tyrosinase inhibitors. The phenolic compounds were extracted using supercritical fluid extraction (SFE) technique following the treatment combinations by response surface methodology (RSM) that investigated the possible interaction between three variables which were pressure (2900 - 4300 psi), temperature (40 - 70 ℃) and extraction time (60 - 120 min). The optimized extraction variables were found at 3800 psi, 53 ℃ and 90 min. The overall model was significant (p < 0.05) with satisfactory R 2 value of 0.9997. The combination of GC-MS and PCA method showed several phenolic compounds were present in the L. domesticum leaves extracts and 2-geranylphenol was predicted to be tyrosinase inhibitor because it showed considerable chemical properties with the control, hydroquinone. The antioxidant activity of the extract was evaluated by DPPH radical scavenging assay using different concentration of L. domesticum leaves extracts. The highest antioxidant activity was observed at 300 ppm of the plant extract. The COSMO-RS result also confirmed that the 2-geranylphenol was successfully extracted by using carbon dioxide as solvent. MEP and molecular docking were done to identify and investigate the key structural features of 2-geranylphenol that are important for their activity and the interaction that contribute to tyrosinase inhibition respectively. The overall result showed that 2-geranylphenol has a potential to replace hydroquinone as tyrosinase inhibitor in cosmetic industry.